Efficacy and Safety of Empagliflozin on Nonalcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis - Zhang, Yuyuan; Liu, Xiaobo; Zhang, Huazhu; Wang, Xuechang (Frontiers in Endocrinology, 2022)
Objective Clinical trials have recently shown a connection between nonalcoholic fatty liver disease (NAFLD) and empagliflozin. This paper aimed at comprehensively assessing the effectiveness and security of empagliflozin in NAFLD patients. Methods PubMed, Embase, Web of Science, Cochrane Library, CNKI, CBM, Wan-Fang digital database, VIP, and WHO ICTRP were searched for randomized controlled trials (RCTs) on the role of empagliflozin in NAFLD from inception to November 2, 2021. For continuous dating, we used values of mean differences (MD) to present. Results A total of four articles involving 244 NAFLD patients were included. Compared with the control group, empagliflozin could significantly reduce the body mass index (BMI) (MD: −0.98 [95% CI: −1.87, −0.10], p = 0.03), liver stiffness measurement (LSM) (MD: 0.49 [95% CI: −0.93, −0.06], p = 0.03), aspartate aminotransferase (AST) (MD: −3.10 [95% CI: −6.18, −0.02], p = 0.05), homeostasis model assessment of insulin resistance (HOMA-IR) (MD: −0.45 [95% CI: −0.90, 0.00], p = 0.05) of the treatment group. Conclusions Empagliflozin can improve body composition, insulin resistance, and liver fibrosis and decrease the hepatic enzymes in patients with NAFLD. Empagliflozin emerges as a new option for treating patients with NAFLD. However, further research shall determine the efficacy and safety of empagliflozin in NAFLD.